Culture and genome-based analysis of four soil Clostridium isolates reveal their potential for antimicrobial production - Pahalagedara ASNW; Jauregui R; Maclean P; Altermann E; Flint S; Palmer J; Brightwell G; Gupta TB (BioMed Central Ltd, 2021)
BACKGROUND: Soil bacteria are a major source of specialized metabolites including antimicrobial compounds. Yet, one of the most diverse genera of bacteria ubiquitously present in soil, Clostridium, has been largely overlooked in bioactive compound discovery. As Clostridium spp. thrive in extreme environments with their metabolic mechanisms adapted to the harsh conditions, they are likely to synthesize molecules with unknown structures, properties, and functions. Therefore, their potential to synthesize small molecules with biological activities should be of great interest in the search for novel antimicrobial compounds. The current study focused on investigating the antimicrobial potential of four soil Clostridium isolates, FS01, FS2.2 FS03, and FS04, using a genome-led approach, validated by culture-based methods. RESULTS: Conditioned/spent media from all four Clostridium isolates showed varying levels of antimicrobial activity against indicator microorganism; all four isolates significantly inhibited the growth of Pseudomonas aeruginosa. FS01, FS2.2, and FS04 were active against Bacillus mycoides and FS03 reduced the growth of Bacillus cereus. Phylogenetic analysis together with DNA-DNA hybridization (dDDH), average nucleotide identity (ANI), and functional genome distribution (FGD) analyses confirmed that FS01, FS2.2, and FS04 belong to the species Paraclostridium bifermentans, Clostridium cadaveris, and Clostridium senegalense respectively, while FS03 may represent a novel species of the genus Clostridium. Bioinformatics analysis using antiSMASH 5.0 predicted the presence of eight biosynthetic gene clusters (BGCs) encoding for the synthesis of ribosomally synthesized post-translationally modified peptides (RiPPs) and non-ribosomal peptides (NRPs) in four genomes. All predicted BGCs showed no similarity with any known BGCs suggesting novelty of the molecules from those predicted gene clusters. In addition, the analysis of genomes for putative virulence factors revealed the presence of four putative Clostridium toxin related genes in FS01 and FS2.2 genomes. No genes associated with the main Clostridium toxins were identified in the FS03 and FS04 genomes. CONCLUSIONS: The presence of BGCs encoding for uncharacterized RiPPs and NRPSs in the genomes of antagonistic Clostridium spp. isolated from farm soil indicated their potential to produce novel secondary metabolites. This study serves as a basis for the identification and characterization of potent antimicrobials from these soil Clostridium spp. and expands the current knowledge base, encouraging future research into bioactive compound production in members of the genus Clostridium.
Keywords: Antimicrobial; Biosynthesis gene clusters; Clostridium spp.; Genome mining; Non-ribosomal peptides; Ribosomally synthesized post-translationally modified peptides; Anti-Infective Agents; Bacillus; Clostridium; Phylogeny; Soil